The flather hydraulic dynomometer - Smith, Oliver Russell (My University, 1898)
Introduction: The Flather Hydraulic Dynamometer is a form of transmitting dynamometer which was first constructed by Prof Flather, of Purdue University. The following is a description of the one owned by the Mechanical Department of the Kansas State Agricultural College. A hollow shaft carries three eighteen inch pulleys. One of these is fixed rigidly to the shaft, and one is entirely loose so that it can turn on the shaft. These two act as ordinary fast-and-loose pulleys, by means of which power can be transmitted by the dynamometer or not, as required. The third pulley is fixed to the shaft by a device for measuring the force required to turn the pulley, and hence, the force required to run any machine to which this pulley may be belted. Fixed to the shaft at the side of this pulley, are two cups opposite each other. Each of these cups is accurately turned inside to receive a plunger, and they are pivoted so that they can have a small motion of rotation in a plane perpendicular to the axis of the shaft. They are so placed that the open end of each is in the direction of rotation of the shaft. There is a hole in the bottom of each cup, which is connected by a flexible tube, to the inside of the hollow shaft.
Citation: Smith, Oliver Russell. The flather hydraulic dynomometer. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Flather Hydraulic Dynamometer; Kansas State Agricultural College; Pulley; Theses; Manuscripts (documents)